A multi-scale analysis of possible conflicts between climate change mitigation and adaptation initiatives in the building industry and human settlement. (29th December 2010) - Kua, H.W.; Gunawansa, A.
Current initiatives to deal with climate change no longer focus entirely on mitigation. Adaptation to climate change is now receiving much needed attention. However, many scholars are concerned over possible conflicts between mitigation and adaptation policies, due to the discrepancies in various operational scales of the two approaches. Using the building industry and urban development as the focus area, we argue that this is not necessarily the case, as mitigation and adaptation can be practiced over multiple scales and levels. We caution that there can actually be six possible types of conflict between mitigation and adaptation policies and legislations in the building industry and urban development, based on the various combinations of scales of mitigation and adaptation. Based on the analysis of such possible conflicts, in this paper, we propose how integrated policies could be designed and implemented to tackle negative and 'unanticipated' policy outcomes in the future.